Software architecture fundamentals : understanding key responsibilities, characteristics, and patterns (O'Reilly Media, 2017)
"Being a successful software architect is more than just possessing technical knowledge. It's about thinking like an architect, being a leader, and understanding the architectural elements, patterns, and styles necessary to create effective software architectures. In this full update to their "Software Architecture Fundamentals 2015" (O'Reilly Media) video course, Neal Ford and Mark Richards empower you with the essential skills you need to be effective in this role. You'll be introduced to previously unmentioned architecture patterns, such as command query responsibility segregation (CQRS) and LMAX, along with the most effective tools and strategies for analyzing architecture. This video is designed for senior-level developers who want to become software architects and for junior architects who want to bump up their skill sets."--Resource description page